A new species of the swarming social wasp chartergellus bequaert, 1938 (Vespidae: Polistinae: Epiponini) from Acre, Brazil - Somavilla, Alexandre; Andena, Sérgio Ricardo (Sociobiology, 2019)
A new species, Chartergellus flavoscutellatus, collected in Acre, Northern Region of Brazil, is described and comparative remarks are given. © 2019 Universidade Estadual de Feira de Santana. All rights reserved.